A new species of Trechalea Thorell, 1869 (Araneae: Lycosoidea: Trechaleidae: Trechaleinae) from Costa Rica, with notes on its natural history and ecology - Da Silva, Estevam L. Cruz; Lapinski, Witold (Zootaxa, 2012)
The genus Trechalea Thorell, 1869 was revised by Carico (1993), who redescribed the eight species known at that time and described two new species, Trechalea boliviensis Carico, 1993 and Trechalea lomalinda Carico, 1993, which were recently transferred to Syntrechalea F.O. Pickard-Cambridge, 1902 by Silva et al. (2012). Presently, the genus comprises eight species, distributed from Southern Arizona, USA to Northern Argentina (Platnick 2012). Other taxonomic papers on Trechalea were made by Carico (2008b), who described male of T. trinidadensis Carico, 1993, and Carico & Silva (2010) who described a new species, T. rothi Carico & Silva, 2010, from Colombia. Both species were synonymized by Silva & Lise (2010) with T. amazonica F.O. Pickard-Cambridge, 1903.